Analisis Faktor-faktor Yang Mempengaruhi Perilaku Ibu Hamil Dalam Pemanfaatan Pelayanan Antenatal Care (K4) Di Wilayah Kerja Puskesmas Pancur Batu Tahun 2023 - Dealita Khairani Daulay; Balqis Nurmauli Damanik; Asnita Yani (Prodi D3 Farmasi Politeknik Katolik Mangunwijaya, 2025)
One of the efforts made to reduce MMR is the Antenatal Care (ANC) examination program which is mandatory for pregnant women. Antenatal care (ANC) is a planned program in the form of observation, education and medical treatment for pregnant women, to achieve a safe and satisfactory pregnancy process and preparation for childbirth. The aim of this research is to determine the factors that influence the behavior of pregnant women in the use of Antenatal Care (K4) services in the Pancur Batu Community Health Center Work Area in 2023. This research uses a descriptive analytical design using quantitative methods with a cross sectional research design approach. The number of samples in this study was 62 respondents. The conclusion of this study is that there is a relationship between maternal knowledge of integrated antenatal care, p = 0.010 (p < a or 0.010 < 0.05). There is a relationship between the Role of the Family in Integrated Antenatal Care, p= 0.001 (p < a or 0.001 < 0.05). It is recommended that pregnant women pay more attention to their pregnancy, namely by making regular integrated antenatal care visits so that the mother's pregnancy can be monitored by health workers.